PESANTREN-BASED MADRASAH MANAGEMENT - Fatah Syukur (Al-Albab, 2012)
Historically, the existence of madrasah can be separated from the development of pesantren in Indonesia. The rise of pesantren, as an effort to modernize the classical educational system as well as the response to the ethical politics of the colonial government, gradually got attention from community members. Nevertheless, this does not mean that madrasah developed without any problems. As an education institution, the madrasah wanted to reach progress like that of public schools. Legally, there are a number of regulations enacted to make the madrasah equal to public schools. So far the madrasah is still seen as a ‘second class’ school. Applying a case study on the Madrasah Roudlatul Ulum, Guyangan Pati, Central Java, this article aims to conceptualize and describe a relatively progressive madrasah and even it has a pesantren under its management. Keywords: madrasah, pesantren, management